Coastal, marine or blue tourism governance? Spotting academic trends through a bibliometric analysis - Balestracci, Giulia; Nel-lo-Andreu, Marta Gemma; Gómez, Sílvia (Frontiers in Marine Science, 2025)
Recognising the critical role of oceans in sustainable development, as emphasised by the UN Decade of Ocean Science for Sustainable Development (2021-2030), this study examines the evolution of academic research on blue tourism governance, a growing field situated at the intersection of marine sustainability, tourism development, and ocean governance. Blue tourism—encompassing coastal and marine tourism—is the largest and most economically significant component of the blue economy, yet its governance dimension remains relatively underexplored. To address this gap, a structured bibliometric analysis of Scopus-indexed publications from 1986 to 2024 was undertaken, using VOSviewer to identify conceptual patterns, thematic trends, and institutional contributions related to coastal, marine, and blue tourism governance. The results reveal a sharp increase in research output from 2010, particularly following the adoption of the UN Sustainable Development Goals and the launch of the Ocean Decade. Early literature focused predominantly on economic development and resource use, whereas recent publications increasingly emphasise sustainability, climate change, marine policy, stakeholder engagement, and integrated governance models. The findings also show growing disciplinary convergence, with environmental sciences, economics, and social sciences frequently intersecting in blue tourism governance discourse. This study clarifies the conceptual positioning of blue tourism within the blue economy framework and highlighting the shift towards governance-oriented scholarship. It identifies critical research gaps, such as including the need for adaptive, multilevel governance approaches and offers a foundation for future work aimed at enhancing the sustainability and equity of tourism in marine and coastal regions.